Antioxidant Activity of Water and Ethyl Acetate Fractions of Qust Al Hindi Root (Saussurea lappa) Using DPPH Inhibition Method - Musdalifah, A.; Sukmawati, Sukmawati; Tahir, Masdiana (Universitas Muslim Indonesia, 2024)
Free radicals are molecules that do not have an electron pair in the outer shell, making them highly reactive. Oxidation due to free radicals can be prevented and inhibited by substances, namely antioxidants. Natural antioxidants are obtained from plants or fruits, one of which is Qust al hindi (Saussurea lappa). Qust al hindi is a plant native to India that is used as a traditional medicine. Qust al hindi contains various phytochemical compounds, one of which is flavonoid compounds that function as antioxidants. The purpose of this study was to analyze the antioxidant activity of water and ethyl acetate fractions of qust al hindi plant roots by 1,1-diphenyl-2picrylhydrazyl (DPPH) silencing method using UV-Vis spectrophotometry based on the calculation of IC50 value using GraphPad Prism Application. The results of this study indicate that the water and ethyl acetate fractions of qust al hindi plant roots have antioxidant activity against DPPH free radicals with IC50 values of 203.5 µg/mL; 193.3 µg/mL, respectively, which are included in the very weak and weak antioxidant groups.